Development of rooting method for Juglans regia L. and Corylus avellana L. in vitro shoots - Arabayeva М.М.; Mikhailenko, N.V.; S.V. Kushnarenko, S.B. (Fundamental and Experimental Biology, 2022)
In vitro biotechnologies are widely used to preserve biodiversity and produce high quality planting material. The main problem that hinders the development of micropropagation for nut crops is their low ability to in vitro root formation and the long period of plant adaptation when transferred to a soil substrate. The aseptic shoots of varieties and wild forms of Juglans regia L. and Corylus avellana L. in vitro micropropagated are used as plant material for this study. A comparison was made between two methods of in vitro rooting. For walnut, the use of a two-stage rooting method on Murashige-Skoog agar medium with high concentrations of indolyl 3 butyric acid (10 mg/l) and sucrose (60 g/l) (method I) made it possible to obtain an average of 68.6 % of rooted plants. The second rooting method, replacing agar with vermiculite, proved to be the most effective for hazelnut, with 91.3 % of Corylus avellana shoots rooting in vitro. The adaptation of hazelnut plants to the conditions of the greenhouse was successful, 91.8 % of the plants continued their development. In walnut, 28.6 % of plants adapted to the soil substrate.